The Effect of Audiovisual Educational Media About Gentle Birth on Pregnancy Readiness for Delivery in the Thirty Trimester of Pregnant Women - Endah Purwanti Handayani; Eftyaningrum Eftyaningrum; Fenny Dinge; Rachel De Fretes (Indonesian Journal of Global Health Research, 2026)
Childbirth preparedness is a critical factor influencing maternal and infant outcomes. However, many pregnant women in their third trimester still experience low levels of preparedness due to a lack of knowledge and high levels of anxiety. Therefore, innovative educational methods such as audiovisual media based on the concept of gentle birth are needed to improve childbirth readiness. This study aims to analyze the effect of audiovisual educational media about gentle birth on childbirth readiness in third-trimester pregnant women at the AHBS Sentani Clinic. This study used a quasi-experimental design with a pretest-posttest approach with a control group design. The study sample consisted of 60 respondents selected using a purposive sampling technique and divided into intervention and control groups of 30 people each. The intervention group was given education using audiovisual media about gentle birth, while the control group was given conventional education. Data dikumpulkan menggunakan kuesioner kesiapan persalinan yang telah diuji validitas dan reliabilitasnya. Analisis data menggunakan uji paired t-test dan independent t-test dengan tingkat signifikansi p < 0 ,05. The results of the study showed a significant increase in childbirth readiness in the intervention group after the intervention (the mean score increased from 1.73 ± 0.70 to 2.47 ± 0.63; p = 0.001). Meanwhile, in the control group there was no significant increase (p = 0.084). There was also a significant difference between the intervention and control groups after the intervention (p = 0.002). Audiovisual educational media about gentle birth has a significant effect on increasing childbirth readiness in pregnant women in the third trimester.